Formation of Professional Competence of University Students Based on a Systematic Approach - Issakova, Gulnur; Kaltayeva, Gulnar; Bakhtiyarova, Gulshat; Ibrayeva, Kulyan; Kudaibergenova, Sayagul (International Journal of Emerging Technologies in Learning (iJET), 2021)
The purpose of this article is to demonstrate the feasibility and effectiveness of a systematic approach to the formation of professional competence of students in higher educational institutions. The study was conducted in the S. Seifullin Ka-zakh Agro Technical University with the participation of 126 master students (2 groups) of the specialty “Vocational Education”. Using a complex of theoretical, empirical and statistical methods, it was possible to show the ways to increase the effectiveness of the educational process. The basic principles for the training of students were formulated as: 1) systematic approach to the formation of profes-sional competence, organization and implementation of the educational process; 2) program-targeted formation of the indicative basis of the upcoming profes-sional activity, and 3) creating a competency model of the corresponding special-ist as a hierarchy of the student’s professional competency system, its subsys-tems, and supersystems. It is recommended that Kazakhstan universities should improve tools and procedures for assessing and monitoring students’ level of knowledge, as well as create new programs for developing students’ professional competencies to ensure their successful employment. The further research on the matter may be the systematic comparative study of contemporary teaching methods and techniques to determine the most productive ways to prepare future pro-fessionals.